Analisis studi kelayakan bisnis pada pangkalan gas LPG “Suliati” di Desa Kemantren Kecamatan Jabung Kabupaten Malang - Arrozaq, Diwika Fatah; Ulum, Ima Fidatul (Maliki Interdisciplinary Journal, 2024)
With the government stopping kerosene subsidies, consumers are switching to LPG gas because it is considered cheaper, this increases demand for LPG gas due to high demand. Now almost everyone uses gas as fuel. The aim of this research is to evaluate the sustainability and feasibility of the "Suliati" 3kg LPG Gas Base Business as a business opportunity. This research approach is descriptive, where the researcher tries to describe and explain the events studied based on survey data. The results of this research are that the "Suliati" LPG Gas Base business is said to be feasible in terms of legal, environmental, market and marketing, technical and technological, financial management and HR and AMDAL aspects.